Chapter Are Italian youngsters adequately equipped for an after-pandemic upswing? - Bollani, Luigi (Proceedings e report, 2023)
Are Italian youngsters adequately equipped for an after-pandemic upswing?All over the world young people seem to be particularly dazed by the Covid-19 pandemic. Indeed, they were touched just lightly by the disease, though the isolation due to the distancing need and the remote learning mode may be the sources of depressive ailments and other psychological distresses. In this paper we analyse the data collected through a survey conducted in the second half of 2021 among a convenience sample of Italian adults. The survey was aimed at highlighting how Italians experienced the pandemic and the way they perceived their futures. About one third of the sample was below 35 and we consider them the young. Most of them were students, a few worked, some were looking for a job. The analysis of the collected data shows that so many young Italians were disturbed by the pandemic, even though the sanitary impact of the disease on them was much less relevant than other age classes. Among the youngsters, the depression and anxiety rates was significantly higher than other adults, the perception of a future role was limited to them and their potential resources for future life was also jeopardized. The possible causes of the reduction capacity among young adults was scouted through a multivariate statistical analysis. It showed that the perception of personal difficulties is correlated to a feeling of uncertainty for their future roles, to a pressure over their social-economical and personal resources to face their future and to a sort of apathy that could limit their pro-activeness.